Pollution and the abundance of plankton in Rangkui River in Bangka Island - Nurtjahya, Eddy; Nashriah, Thoibatun; Lukman, Lukman (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Land use and activity around the Rangkui Watershed affect water quality, and plankton have been studied to help manage the river's water quality. In the 2017 dry season, six station points representing land use functions from upstream to downstream were studied. Surface water sampling was carried out during the day with three replicates. Pollution around the Rangkui Watershed affected plankton abundance. Based on saprobity and physicochemical readings, the pollution level ranged from light upstream to heavy downstream. This study found 15 species from 15 families from six phytoplankton classes, that is, Bacillariophyceae, Chlorophyceae, Euglenophyceae, Cyanophyceae, Cryptophyceae, Dinophyceae, and 2 species of zooplankton Eurotatoria, and Branchiopoda. The highest total abundance of phytoplankton and zooplankton was observed upstream of Station 1 (721 ind/L) and gradually decreased downstream, with the exception of the absence of plankton at Station 3. Nitrate had a positive correlation with phytoplankton at different correlation levels, whereas other abiotic environments responded differently to phytoplankton and zooplankton. The water quality is highest upstream, where there are pepper plantations, and gradually decreases as it flows downstream. The station near tin mining activities was the most polluted.